Surface Influences on the Electrodiffusive Behavior in Mesoporous Templates. Issue 26 (4th March 2015) - Graf, M.; Poppe, J.; Eychmüller, A.
<x xml:space="preserve">Abstract</x> The physicochemical details of the well‐established template‐assisted electrodeposition process for metal nanowire fabrication are investigated with respect to the physical origination for template geometry limitation. The overall process of metal reduction inside anodized Al2O3 (AAO) is divided into three parts: i) the electrochemical reduction at the pore bottom, ii) the diffusion of the electrolytic species, and iii) the capacitive interaction between pore surface and electrolyte. The results show that the reduction of Ni is controlled by the degree of electrode recession, i.e., the pore depth. Applying Cottrell's equation to pulsed electrodeposition enables experimental access to diffusion coefficients (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1m9q3s3x" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />DNi2+</alternatives>). This gives a gradient in <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1m9q3s2c" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />DNi2+</alternatives> along with the filling process. The switch‐over from crystallization to diffusion control is investigated to depend on temperature and pore length. Additionally, the electrode surface capacitance scales non‐linearly with the pore depth. This is deduced as a consequence of electrostatic surface–electrolyte interaction. A minimum in the electrode capacitance at a pore length of 48 μm is identified as the point with maximum thickness of a double‐layer‐type surface effect to the electrolyte. The results extend the template's role from simply geometrically limiting metal growth and explain occurring process issues when filling especially high‐aspect‐ratio pores.